2009
DOI: 10.1007/s10333-009-0177-7
|View full text |Cite
|
Sign up to set email alerts
|

Application and development of a decision-support system for assessing water shortage and allocation with climate change

Abstract: The assessment to vulnerability of the water supply system needs several modeling tools and cases to simulate. A decision-support tool which integrates the common procedures of impact assessment of climate change, downscaling, weather generation, hydrological model, and interface for linking system dynamics model is proposed here. In this study, the impact of climatic change and growing water demand to the water supply system in Touchien river basin in Taiwan was derived. The vulnerability for the current wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 4 publications
0
14
0
2
Order By: Relevance
“…The current risk is assessed using an integrated risk assessment tool of water resources called TaiWAP [21] and the verified water supply system dynamics model. The result is further quantified with the defined indicators.…”
Section: Current Climate Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The current risk is assessed using an integrated risk assessment tool of water resources called TaiWAP [21] and the verified water supply system dynamics model. The result is further quantified with the defined indicators.…”
Section: Current Climate Risk Assessmentmentioning
confidence: 99%
“…The GCMs with high validity were selected. Moreover, the weather data is generated based on a Richardson-type weather generator [23] using TaiWAP [21], in which the data was downscaled by bias correction [24] and the climate scenarios are setup using the delta method [25]. Then, the risk assessment of the baseline is similarly conducted as the current risk assessment.…”
Section: Baseline Climate Risk Assessmentmentioning
confidence: 99%
“…Past studies have focused on the vulnerability and resilience of water resources and identified adaptation strategies against the impacts of climate change (Liu et al 2009;Urich and Rauch 2014;Tung et al 2014). Brenkert and Malone (2005) assessed the vulnerability of India using a Vulnerability-Resilience Indicator Prototype.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this study is to apply a systematic assessment framework under Taiwan Water Resources Assessment Program to Climate Change (TaiWAP) (Liu et al 2009;Tung et al 2014) and grading indicators to assess the cross-sectorial vulnerability and resilience in Tainan City under climate change. Different adaption measures are then adopted to evaluate their effects on reducing vulnerability and promoting resilience.…”
Section: Introductionmentioning
confidence: 99%
“…With the models, an assessment of the future climate would be possible [2,3], and the problem of uncertainty may be mitigated by considering multiple models [4,5]. According to the results of the cited researches, the rainfall distribution would be different and temperature would rise under climate change.…”
Section: Introductionmentioning
confidence: 99%